2019
DOI: 10.1161/jaha.119.013465
|View full text |Cite
|
Sign up to set email alerts
|

Human Relaxin‐2 Fusion Protein Treatment Prevents and Reverses Isoproterenol‐Induced Hypertrophy and Fibrosis in Mouse Heart

Abstract: Background Heart failure is one of the leading causes of death in Western countries, and there is a need for new therapeutic approaches. Relaxin‐2 is a peptide hormone that mediates pleiotropic cardiovascular effects, including antifibrotic, angiogenic, vasodilatory, antiapoptotic, and anti‐inflammatory effects in vitro and in vivo. Methods and Results We developed RELAX 10, a fusion protein composed of human r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Studies of the effect of INSL3 injections on testicular functions in rats have shown that INSL3 can pass through the blood-testis barrier (Anand- Ivell et al 2009) and protect against GnRH antagonist-induced apoptosis in germ cells (Kawamura et al 2004). Various approaches previously used to improve the stability of relaxin (Muppidi et al 2019, Nagorniewicz et al 2019, Sun et al 2019 can be applied to INSL3 to design biologicals with the full spectrum of INSL3/RXFP2 downstream signaling. Alternatively, small molecule agonists have proven to be an attractive alternative to therapies with peptide ligands due to improved stability and potential oral bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effect of INSL3 injections on testicular functions in rats have shown that INSL3 can pass through the blood-testis barrier (Anand- Ivell et al 2009) and protect against GnRH antagonist-induced apoptosis in germ cells (Kawamura et al 2004). Various approaches previously used to improve the stability of relaxin (Muppidi et al 2019, Nagorniewicz et al 2019, Sun et al 2019 can be applied to INSL3 to design biologicals with the full spectrum of INSL3/RXFP2 downstream signaling. Alternatively, small molecule agonists have proven to be an attractive alternative to therapies with peptide ligands due to improved stability and potential oral bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were reviewed and approved by the Institutional Animal Care and Use Committee (IACUC ID: 17-3256) at Nantong University and performed in accordance with the NIH Guide for the Care and Use of Laboratory Animals. Briefly, the mice were anesthetized with isoflurane (Sigma-Aldrich; Merck KGaA) inhalation at a concentration of 2.5% for anesthetic induction and then at 1.5% for anesthetic maintenance (22)(23)(24). SKOV3 cells (10 6 cells per mouse in 100 µl PBS) were implanted subcutaneously into the right flanks of 6-to 8-week-old female nu/nu mice.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…However, relaxin recently failed to reach its primary endpoint in a phase III clinical trial for acute heart failure 91 . The clinical success of relaxin may be limited due to its short plasma half-life 92 , and several groups have developed lipid and Fc conjugates with relaxin to extend the persistence of exposure in plasma 93 , 94 . An additional concern that may have precluded clinical pursuit of relaxin for anti-cancer treatment is the observation that relaxin signaling is involved in tumor progression and metastasis in several cancers 95 , 96 .…”
Section: Vasculaturementioning
confidence: 99%